Is It a “Colon Perforation”? A Case Report and Review of the Literature - Lu, Shuangshuang; Yao, Xinyu; Shi, Jun; Huang, Jian; Zhuang, Shaohua; Ma, Junfang; Liu, Yan; Zhang, Wei; Yu, Lifei; Zhu, Ping; Zhu, Qiuwei; Shi, Ruxia; et al. (Frontiers in Medicine, 2022)
Background: Intrauterine devices (IUDs) are commonly used as a contraceptive method. IUD migration and colon perforation are rare but serious complications occurring sometimes years after insertion. Case: A 42-year-old woman with complaints of slight abdominal pain underwent a colonoscopy. Colonoscopy showed that a “nail” had penetrated the ascending colon wall and that an arm of the “nail” was embedded in the colon wall. We did not remove the “nail” rashly under colonoscopy. Considering the safety and effectiveness of the patient's operation, we were able to remove the “nail” easily by performing laparoscopic-endoscopic cooperative surgery (LECS) combined with hysteroscopy at the same time. Conclusion: We report a case of successful removal of a colonic perforation device by colonoscopy, laparoscopy, and hysteroscopy, which is the first method used.